Decyzje biznesowe oparte na inteligentnych narzędziach analitycznych - Bartuś, Kamila; Bartuś, Tomasz (Business Decisions Supported by Intelligent Analytical Tools, 2005)
The aim of the article is to analyze selected tools which support business decision making. The paper presents the process of supplying data warehouses, the OLAP tools and data exploration. Further on, the architecture and examples of Business Intelligence system implementation have been described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 194-202